2019
DOI: 10.1515/ijamh-2019-0157
|View full text |Cite
|
Sign up to set email alerts
|

Substance abuse in adolescents before admission to Peruvian juvenile detention centers: results from a national census in Peru, 2016

Abstract: Objectives To estimate the prevalence of drug use before admission to juvenile detention centers (JDC) in Peru and determine individual, family and social influences on behavior. Methods A cross-sectional analysis was performed using data from the 2016 National Population Census in Juvenile Detention Centers (NPCJDC). A total of 1960 Peruvian adolescent offenders were included. Generalized linear models of the Poisson family with a log link function were used to determine if characteristics before admission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…A secondary analysis of data from Florida Youth Substance Abuse Survey in 2014 revealed that certain unlawful and precarious behaviors are linked to the use of alcohol and marijuana (Sharp et al 2019). Similarly, the 2016 National Population Census in Peruvian Juvenile Detention Centers indicated that over a half of juvenile delinquents in Peru reported substance abuse, with cannabis being the most abused substance (Vargas-Fernández et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A secondary analysis of data from Florida Youth Substance Abuse Survey in 2014 revealed that certain unlawful and precarious behaviors are linked to the use of alcohol and marijuana (Sharp et al 2019). Similarly, the 2016 National Population Census in Peruvian Juvenile Detention Centers indicated that over a half of juvenile delinquents in Peru reported substance abuse, with cannabis being the most abused substance (Vargas-Fernández et al 2019).…”
Section: Introductionmentioning
confidence: 99%